Evaluation of the effectiveness and efficiency of Wagner and Fischer algorithm in retrieving Hadith translated documents / Kamarul Arifin Muhamad - Muhamad, Kamarul Arifin (2002)
Information technology has enabled information that can be in many forms such as text, image or sound, to be accessed widely using search terms via a computer. Due to this type of popularity and advanced in technology, there is an increased interest in searching Malay text to enable scholars and researchers to access the data on-line. This thesis studies the method of a string-searching algorithm. The studies describe features and methods for string searching and comparison using Wagner and Fischer algorithm. This thesis concerns a Malay language documents retrieval system. The method is used in developing search engine because of its speed and efficiency since it is based on dynamic programming. Dynamic programming is used to solve Edit Distance problem. The approach has two main sections: the methodology used in implementing, and the result. The methodology used in implementing contains the checking step, and the calculation of Dice coëfficiënt. The result is the produced result from experiment. The method has been implemented as a C programming language. In this study, Wagner and Fischer algorithm, Hadith test collection that consists of Malay Hadith translation documents, query words and relevant judgements are used. The Wagner and Fischer are used to retrieve documents from translated Hadith. Before the experiments can be performed, the Hadith test collections must be built first. Two types of experiments are conducted. First experiment uses exact match, which is no method, is apply. Second experiment uses dynamic programmings apply with Wagner and Fischer algorithm.